2015
DOI: 10.1128/jcm.01369-15
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Mapping as a Novel High-Resolution Typing Tool for Legionella pneumophila

Abstract: bLegionella is the causative agent for Legionnaires' disease (LD) and is responsible for several large outbreaks in the world. More than 90% of LD cases are caused by Legionella pneumophila, and studies on the origin and transmission routes of this pathogen rely on adequate molecular characterization of isolates. Current typing of L. pneumophila mainly depends on sequence-based typing (SBT). However, studies have shown that in some outbreak situations, SBT does not have sufficient discriminatory power to disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…On the other hand, the occurrence of same L. pneumophila STs in the environmental samples poses a risk, and sustainable monitoring of hospital water systems is recommended [33]. Nowadays, WGS has been successfully applied for L. pneumophila providing the highest conceivable discriminatory power to distinguish outbreak from non-outbreak isolates [34, 35]. To this end, further genomic and metagenomics studies are needed using DNA from the clinical and environmental samples used in this study [36].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the occurrence of same L. pneumophila STs in the environmental samples poses a risk, and sustainable monitoring of hospital water systems is recommended [33]. Nowadays, WGS has been successfully applied for L. pneumophila providing the highest conceivable discriminatory power to distinguish outbreak from non-outbreak isolates [34, 35]. To this end, further genomic and metagenomics studies are needed using DNA from the clinical and environmental samples used in this study [36].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, whole genome sequencing (WGS) has been applied to subtype various pathogens including L. pneumophila . For L. pneumophila subtyping, WGS-based methods provided better discriminatory power to distinguish outbreak isolates from non-outbreak isolates 17 19 20 21 .…”
mentioning
confidence: 99%
“…Although there have been many studies probing new typing methods for L . pneumophila , such as SNP-based approach [ 56 ], whole-genome mapping (WGM) [ 17 ], cgMLST [ 13 , 50 ] and rMLST [ 59 ], these schemes required to sequence a great many of gene loci, and the cost and bioinformatics infrastructure might be issues in some laboratories. In this study, we reported a five-gene MLST scheme for genotyping of L .…”
Section: Discussionmentioning
confidence: 99%
“…For example, subtyping the isolates belonging to a same prevalent ST required combinatory approach, including PFGE, AFLP, monoclonal antibody-based (MAb) subgrouping and some other genome sequence-based typing schemes [ 14 – 16 ]. A large proportion of LD cases is caused by just a small number of common STs (e.g., ST1); the SBT can lack discriminatory power [ 13 , 17 , 18 ]. Therefore, research and improvement of molecular typing methods for L .…”
Section: Introductionmentioning
confidence: 99%